ANALISIS KESEHATAN KOPERASI SIMPAN PINJAM BAKALIKAT SUMBA TIMUR - Vindya Donna Adindarena, Thomas de Aquino Tomy Kelen (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2017)
This study is aimed at analyzing the health level of KSP Bakalikat, one of the cooperatives in Sumba Timur. From 2011 and 2016, there is an increasing number of cooperative forming in Kabupaten Sumba Timur. This condition shows that it is not only the government who holds the responsibility of developing cooperatives but the community also has roles to fulfill. On the other side, this fact shows cooperative also affect the rise of fair and wealthy economic conditions for the members of the cooperatives and also for the community in general. The analysis uses the guidelines from the Peraturan Mentri Koperasi Dan Usaha Kecil Dan Menengah No.20/Per/M.KUKM/XI/2008 to assess 7 aspects in a cooperative. Those aspects are capital, the quality of assets, management, efficiency, liquidity, independence and growth, and the identity of the cooperative. The result shows that KSP Bakalikat Sumba Timur is not a healthy cooperative since the total score obtained is 36,60.